Conflict terminology and concepts used in covering tourism news in directed international radio stations: Al-Hurra channel as a model (Eurasian Journal of Media and Communications, 2023)
International radio is a communication activity with purely political and economic dimensions, because it is an expression of the state's political vision and an extension of this vision. Thus, the aforementioned factors affect the news coverage of world tourism events and their variables. This research is an attempt to discover these factors that can affect the news coverage of the international radio broadcasts. International radio stations use special terms and concepts that reflect international politics and the positions of the state that constitute the reference for the directed radio, and these countries employ the tourism field to form certain trends. This research attempts to reveal them, in order to deepen the understanding of the work of directed international broadcasts and to build a balanced international communication. The researcher chose the subject of tourism as a field of interest to international broadcasters for several considerations